International suicide rates and prevention strategies - De Leo, Diego (Hogrefe & Huber, 2004)
This book analyzes the latest trends in suicide rates and attempts around the world using data from the WHO's Mortality Database. It covers the whole life span from childhood (under 15 years) through to late adulthood (65 years and over). This comprehensive examination of international trends pro-vides a uniquely clear picture of suicide mortality in the last half century, with an emphasis on recent and emerging trends. Controversially, the book then goes on to examine the impact of national suicide prevention strate-gies, national mental health plans, substance use policies, and the use of antidepressant medications on suicide mortality, providing some astounding initial data on the efficacy - or lack of efficacy - of these activities in the prevention of suicide